Why God is probably good: a response to the evil-god challenge. Issue 3 (September 2021) - MILLER, CALUM
Abstract: A number of philosophers have recently defended the evil-god challenge, which is to explain relevant asymmetries between believing in a perfectly good God and believing in a perfectly evil god, such that the former is more reasonable than the latter. In this article, I offer a number of such reasons. I first suggest that certain conceptions of the ontology of good and evil can offer asymmetries which make theism a simpler hypothesis than 'maltheism'. I then argue that maltheism is itself complex in a variety of ways: it is difficult to articulate a simple precise version of maltheism; maltheism posits a mixture of positive and negative properties; maltheism posits a more complex relationship between moral motivation, practical reason and action; and maltheism relevantly parallels other epistemically 'complex' sceptical scenarios.